Irreversibility analysis of radiative flow of Prandtl nanofluid over a stretched surface in Darcy-Forchheimer medium with activation energy and chemical reaction - Syed Sohaib Zafar; Umair Khan; Farhan Ali; Sayed M. Eldin; Abdulkafi Mohammed Saeed; Aurang Zaib; Ahmed M. Galal (Heliyon, 2023)
This communication elaborates the irreversibility analysis of the flow of Prandtl nanofluid along with thermal radiation past a permeable stretched surface embedded in a Darcy-Forchheimer medium. The activation and chemical impressions along with effects of thermophoretic and Brownian motion are as well examined. The flow symmetry of the problem is modeled mathematically and leading equations are rehabilitated into nonlinear ordinary differential equations (ODEs) through the assistance of suitable similarity variables. The Keller-box technique in MATLAB is employed to draw the impacts of the contributing elements on the velocity field, temperature distribution, and concentration. The impact of the Prandtl fluid parameter has mounting performance for the velocity whereas conflicting behavior is examined in the temperature profile. The achieved numerical results are matched correspondingly with the present symmetrical solutions in restrictive cases and fantastic agreement is scrutinized. In addition, the entropy generation uplifts for the growing values of the Prandtl fluid parameter, thermal radiation, and Brinkman number and decreases for growing numbers of the inertia coefficient parameter. It is also discovered that the coefficient of friction decreases for all parameters involved in the momentum equation. Features of nanofluids can be found in a variety of real-world fields, including microfluidics, industry, transportation, the military, and medicine.